Evaluating the potential and development of mount telomoyo as a sustainable tourism attraction in central Java - Winarni, Isti; Un, Lakna Tulas; Shbair, Ahmed (Indonesian Tourism Journal, 2024)
The research investigates the diverse potential attractions of Mount Telomoyo, a natural tourist destination in Central Java, Indonesia. With a growing number of visitors each year, this study aims to analyze the key components that contribute to its appeal. Utilizing qualitative methods, including interviews, observations, and documentation, the research identifies four main components of attraction: natural beauty, cultural significance, accessibility, and amenities. The natural allure of Mount Telomoyo is heightened by its stunning landscapes, surrounded by prominent mountains and offering panoramic views of Rawa Pening and nearby cities. Culturally, the site hosts annual traditional events such as the Saparan ceremony, reflecting the local community's cultural heritage. Accessibility is also a significant factor, with easy routes to the peak, facilitated by available transportation services. Moreover, the amenities provided, including accommodations, dining options, and organized tours, enhance the overall visitor experience. The study concludes that Mount Telomoyo’s tourism potential is distinguished by its combination of natural, cultural, and man-made attractions, supported by accessible infrastructure and comprehensive services. These findings suggest that continuous development and management are essential to sustaining and increasing tourist interest in the region.